2017
DOI: 10.1007/s40273-017-0558-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Survival Outcomes of Immuno-Oncology Drugs in Economic Evaluations: A Systematic Approach to Data Analysis and Extrapolation

Abstract: Background New immuno-oncology (I-O) therapies that harness the immune system to fight cancer call for a reexamination of the traditional parametric techniques used to model survival from clinical trial data. More flexible approaches are needed to capture the characteristic I-O pattern of delayed treatment effects and, for a subset of patients, the plateau of long-term survival. Objectives Using a systematic approach to data management and analysis, the study assessed the applicability of traditional and flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 30 publications
1
73
0
Order By: Relevance
“…RCS models are polynomial functions fitted to segmented portions of the data at points known as knots, which define the degree of smoothness of the data fit 35 . Survival analysis applied to CheckMate 067 data found that RCS models performed better than conventional functions in terms of goodness-of-fit and coherence, with longer term data, as supported by research conducted by Gibson et al 14…”
Section: Baseline Characteristics and Regression Analysesmentioning
confidence: 54%
See 3 more Smart Citations
“…RCS models are polynomial functions fitted to segmented portions of the data at points known as knots, which define the degree of smoothness of the data fit 35 . Survival analysis applied to CheckMate 067 data found that RCS models performed better than conventional functions in terms of goodness-of-fit and coherence, with longer term data, as supported by research conducted by Gibson et al 14…”
Section: Baseline Characteristics and Regression Analysesmentioning
confidence: 54%
“…This paper extends a program of research being undertaken on innovative approaches to economic modeling and more accurate survival extrapolation 14 in I-O to represent clinical trial and long-term observational data in a more meaningful way. It builds on a previous comparison 15 of the 3-state PSM and extensions thereof vs a Markov modeling approach (a commonly used structure in health care evaluations) to represent I-O therapies ( Figure 2).…”
Section: Study Questionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is an extensive literature on modelling time-to-event data, including standard parametric models that are members of the generalised F distribution [22], flexible parametric models [23], piecewise models, and mixture models which include the standard cure rate model as a special case [24], and a growing body of work in the health economic literature on fitting parametric survival functions to time-to-event data [25][26][27][28][29], combining evidence on time-to-event outcomes across multiple clinical trials [30][31][32], and on incorporating external information in addition to sample data [33,34]. A limitation with standard parametric models is that they only capture certain shapes for the hazard function; for example, the hazard function of a generalised F distribution can be only decreasing, decreasing but not necessarily monotone and arc shaped, while the hazard function of the generalised gamma subfamily can be only monotonically increasing and decreasing, bathtub and arc-shaped.…”
Section: Parameter Estimationmentioning
confidence: 99%